DEVELOPMENT OF FLOUR COMBINED SYSTEMS WITH IMPROVED AMINO ACID COMPOSITION - T. Matveeva; V. Papchenko; P. Petik; V. Khareba; O. Khareba (Harčova Nauka ì Tehnologìâ, 2023)
Questions of mathematical calculation of combined flour systems with improved amino acid composition have been studied. To create such systems, it is proposed to use secondary products of oilseeds processing – meal, namely soybean, linseed and sunflower. The expediency of using the indicated meals is substantiated. It is emphasized that in order to create scientific foundations and practical directions for the use of new raw materials in the production of flour products, comprehensive studies are needed to study its composition, physical and chemical properties, as well as the impact on the quality of finished products. The amino acid composition of the proteins of these meals and wheat flour was experimentally determined. Calculated amino acid score. Particular attention is paid to the mathematical calculation of the composition of oilseed meal, which, in terms of amino acid composition, is as close as possible to the reference protein. The mass fractions of soybean, flaxseed and sunflower meal proteins in the composition were determined, namely: 0.51, 0.2 and 0.29, respectively. The amino acid composition and the biological value of the protein of the obtained meal composition were established. It was shown that for such amino acids as lysine, the amount of sulphurous (methionine + cystine) and threonine amino acid score of combined flour systems increased by 0.7–2 times compared to that of wheat flour. The ratio of soybean, linseed and sunflower meal in the composition of the improved amino acid composition in percentage terms was obtained: 44:25:31. Mathematically calculated the content and rate of essential amino acids in systems, which in their composition contain 90–80% wheat flour and 10–20% composition of oilseed meal. The results of studies of such systems showed that the moisture index is almost the same, and the acidity index is slightly higher than the index (4.68 versus 3.03 degrees) for premium wheat flour. Trial baking of bread was carried out, it’s organoleptic, and physico-chemical parameters were determined in comparison with bread based on premium wheat flour. In a bread sample based on combined flour systems, the moisture content is 39.34%; porosity – 77.15%; acidity – 1.83 degrees. The characteristics of the developed systems make it easy to introduce it into the technological process of existing enterprises for the production of bakery products.